Pengaruh peran Aparat pengawas Internal pemerintah (APIP) Dalam pelaksanaan Maturitas sistem Pengendalian internal PEMERINTAH (SPIP) Inspektorat kota pekalongan - Karmanis Karmanis; Aan Cholifah Rofa’a (Jurnal Media Administrasi, 2021)
One type of local government supervision is internal control. This internal control is carried out by the government internal control apparatus (APIP) at the Regional Inspectorate. The main role of APIP is as a consultant and problem solver for local governments with the task of conducting inspections, reviews, monitoring and evaluation, as well as other supervision of the implementation of tasks and functions of local government organizations.This type of research is descriptive using a qualitative approach. The location chosen for this research is the Inspectorate of Pekalongan City. The data source retrieval technique in this study uses data triangulation techniques. Meanwhile, the focus of this research is on examining the influence of APIP's role in the implementation of the maturity of the Government Internal Control System (SPIP) at the Pekalongan City Inspectorate.The results of this study are (1) the Pekalongan City Inspectorate performs its role as a leader who is the forefront funnel by coordinating, carrying out control functions, encouraging the creation of bureaucratic reform and governance, (2) Pekalongan City Inspectorate has an Internal Supervision function which includes activities that include: directly related to quality assurance that supports the implementation of an effective, transparent, accountable and clean government from KKN practices, (3) As a consultant to the Pekalongan City Inspectorate must know more than the party conducting consultations regarding regional financial management in accordance with the laws and regulations that exist, (4) Government Internal Supervisory Apparatus plays a role as Quality Assurance, namely ensuring that an activity can run efficiently, effectively and in accordance with the rules in achieving organizational goals, and (5) The role of the auditor as a catalyst based on employee perceptions influence on the achievement of the goals of the organization.